Financial Development, Financial Instability and Economic Growth: The Case of Maghreb Countries - Khattab, Ahmed; Mathieu Juliot, Mpabe Bodjongo; Abid, Ihadiyan (International Journal of Economics and Financial Issues, 2015)
The objective of this article consists in examining the interactions between the financial development, financial instability and economic growth in the Maghreb countries. The analysis covering the period of 1995-2013 relates to a sample of five countries of the region. By using the World Bank data (2013) and the Heritage Foundation data (2013), the panel VAR model estimation revealed that (a) the financial development has positive effects on itself but a negative impact on the financial instability as well as a combined impact on the economic growth. (b) The financial instability has a negative impact on the financial development, a positive impact on itself and a combined effect on the economic growth. (c) The economic growth promotes the financial development and the financial instability; it has also a positive effect on itself. (d) Finally, the financial liberalization in a less corrupt environment promotes the financial development. Keywords: Financial development; financial instability; economic growth JEL Classifications: E44; G10; O16; O50